INOVASI MODEL PEMBELAJARAN PAUD DIMASA PANDEMIC COVID-19 DI TK AISIYAH 1 KESUGIHAN - Ifa Refli Hanita; Inayatul Lathifah (JURNAL WARNA, 2021)
The spread of the covid-19 virus that occurred in Indonesia caused changes in the education sector, especially in the learning process which initially used a face-to-face form to now learn in an online form. As a result, educators are encouraged to be able to make innovations in learning models that will be applied to their students. This study aims to find out some of the innovations used in Kindergarten Aisiyah 1 Kesugihan. This research method is descriptive qualitative. Data collection techniques in this study are interviews, observations, and supporting documents. The results of this study indicate that 1) learning in kindergarten has changed in the interactivity between educators and students 2) The learning process at Kindergarten Aisiyah Bustanul Athfal 1 Kesugihan uses partly online and partly offline learning, 3) Several innovations are made, namely involving parents when learning activities, using android-based learning media and learning oriented to student activity. 4) learning innovation is obtained from the creativity of educators by using active, creative, effective and fun learning. 5) making learning innovations, educators pay attention to several things 6) The assessment is through photos or videos containing assignments sent by students via online, 7) there are several obstacles when learning online 8) educators overcome them by repeating the material at a glance.